Tinjauan Hukum Persaingan Usaha dalam Praktek Persekongkolan Tender (Studi Putusan Nomor:04/KPPU-L/2018) - Rendi Ardiansyah; Margo Hadi Pura (Universitas Batanghari Jambi, 2021)
The existence of Law Number 5 Year 1999 is expected to prevent monopolistic practices and unfair business competition in a business world that continues to develop with increasingly fierce competition. However, until now there are still many unfair effort practices because increasingly complex competition and demands for profusely profit, one of which is related to tender conspiracy activities carried out in the procurement of goods and services within the government. Between them are the practice of conspiracy to tender for the Decision of the Business Competition Supervisory Commission Number 04/ KPPU-L/2018. In writing this article using a normative juridical research method in which research and observations are carried out in a library by emphasizing the applicable legal principles. The purpose of writing this article is to find out tender conspiracy in view of business competition law, which is essentially prohibited because it will prevent other business actors from competing in offering prices at the auction. In addition, this article discusses the fulfillment of the formulaic elements in the practice of tender conspiracy in the a quo case. Tender conspiracy is specifically regulated in Article 22 of Law Number 5 Year 1999 which is then complemented by the guidelines issuance of Article 22 by KPPU. Whereas in essence the actions of the Reported Parties in the implementation of the a quo tender constituted a tender conspiracy practice because they had complied with all the elements referred to in Article 22 of Law Number 5 Year 1999 resulting in receiving administrative sanctions imposed by KPPU as a form of law enforcement.